2020
DOI: 10.4273/ijvss.12.3.14
|View full text |Cite
|
Sign up to set email alerts
|

Development of Taguchi based Grey Relational Analysis Optimization for FSW of AZ31B Magnesium Alloy

Abstract: In this paper, grey relational analysis combined with Taguchi method has been used to evaluate the weld ability of AZ31B magnesium alloy by FSW process. The L9 Taguchi design considering an orthogonal array consists of 3 factors and 3 levels was used for experimentation. The rotational speed of tool, transverse speed and angle of tilt of the tool are selected as welding parameters. The welding parameters influence on responses namely Ultimate Tensile Strength (UTS) and hardness has been analyzed using ANOVA. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Unnikrishnan et al 38 showed that gray relational analysis combined with L 9 consists of three factors and three levels of Taguchi method was taken to experimentally evaluate the weld ability of AZ31B magnesium alloy by FSW process. As a result, during confirmation test, it showed that better results in the optimization of welding parameters in FSW of AZ31B magnesium alloy was obtained through gray relational analysis along with Taguchi based method.…”
Section: Introductionmentioning
confidence: 99%
“…Unnikrishnan et al 38 showed that gray relational analysis combined with L 9 consists of three factors and three levels of Taguchi method was taken to experimentally evaluate the weld ability of AZ31B magnesium alloy by FSW process. As a result, during confirmation test, it showed that better results in the optimization of welding parameters in FSW of AZ31B magnesium alloy was obtained through gray relational analysis along with Taguchi based method.…”
Section: Introductionmentioning
confidence: 99%